Advanced treatment of biologically treated medium density fiberboard (MDF) wastewater with Fenton and Fenton enhanced hydrodynamic cavitation process - Balcik-Canbolat, Cigdem; Sakar, Hacer; Karagündüz, Ahmet; Keskinler, Bülent (Wiley-Blackwell, 2016)
BACKGROUND: Biological treatment processes are often ineffective for the treatment of medium density fiberboard (MDF) wastewater due the presence of non-biodegradable and refractory compounds. Fenton and Fenton enhanced hydrodynamic cavitation (HC) processes may be cost effective solutions for the treatment of such wastewater. RESULTS: Removals of COD, formaldehyde and color by Fenton and Fenton enhanced HC processes were investigated in this study. The optimum H2O2/Fe2+ molar ratio at the initial pH of 3 for the optimum COD removal efficiency was 2.5/1 in 70 min reaction time. Furthermore, faster removal rates of pollutants were also observed with HC enhanced Fenton process. The presence of various herbicides and fungicides in the wastewater were detected by gas chromatography/mass spectrometry (GC/MS). CONCLUSIONS: The Fenton enhanced process resulted in faster COD removal rates than those obtained in Fenton alone. The Fenton enhanced HC process appears to be a cost-effective alternative for the treatment of highly toxic and non-biodegradable MDF wastewater. (C) 2016 Society of Chemical Industry
Keywords: Fenton process; hydrodynamic cavitation; medium density fiberboard wastewater; formaldehyde removal